2013
DOI: 10.1681/asn.2012080875
|View full text |Cite|
|
Sign up to set email alerts
|

High-Efficiency Postdilution Online Hemodiafiltration Reduces All-Cause Mortality in Hemodialysis Patients

Abstract: Retrospective studies suggest that online hemodiafiltration (OL-HDF) may reduce the risk of mortality compared with standard hemodialysis in patients with ESRD. We conducted a multicenter, open-label, randomized controlled trial in which we assigned 906 chronic hemodialysis patients either to continue hemodialysis (n=450) or to switch to high-efficiency postdilution OL-HDF (n=456). The primary outcome was all-cause mortality, and secondary outcomes included cardiovascular mortality, all-cause hospitalization, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

32
619
10
30

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 624 publications
(742 citation statements)
references
References 29 publications
32
619
10
30
Order By: Relevance
“…The Turkish HDF and CONTRAST studies found no difference in mortality or cardiovascular events [15,16] whereas the ESHOL study reported a large (30%) reduction in all-cause mortality [17]. This evidence base is further complicated by the divergent results of four meta-analyses, all of which showed reductions in IDH with HDF but only one suggested improved patient outcomes [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Turkish HDF and CONTRAST studies found no difference in mortality or cardiovascular events [15,16] whereas the ESHOL study reported a large (30%) reduction in all-cause mortality [17]. This evidence base is further complicated by the divergent results of four meta-analyses, all of which showed reductions in IDH with HDF but only one suggested improved patient outcomes [11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…On-line haemodiafiltration (HDF) is a modified haemodialysis (HD) modality incorporating increased convective clearance, which has long been reported to reduce intradialytic hypotension (IDH) [11][12][13][14]. However, despite three randomised controlled trials and several meta-analyses, opinion remains conflicted as to whether HDF improves patient outcomes and the mechanisms by which HDF may do so are not well elucidated [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…However, patients, who received a convective volume of >15 l (CONTRAST) or 17.4 l (Turkish online hemodiafiltration study), had a significantly lower mortality rate. This result was confirmed in the ESHOL study, where patients on online HDF had a 30 % lower risk of all-cause mortality [17]. However, a review of the β2-MG levels in these studies (CONTRAST: decrease, Turkish online: unchanged, ESHOL: increase) suggests that it is unlikely that the effect of online HDF on mortality is attributable to the removal of middle molecules only.…”
Section: Introductionmentioning
confidence: 80%
“…On further analysis, the convective volumes used in the ESHOL study were found to be significantly higher compared with the other 2 studies, and a post-hoc analysis of all 3 studies suggests a benefit from HDF over HFHD when higher convective volumes are used. In the case of ESHOL, this was both in the 23.1-25.5 L/treatment cohort and in the >25.4 L/treatment cohort [7] . In CON-TRAST, benefit was seen in the >21.95 L/treatment cohort [8] and in the Turkish study >19.5 L/treatment [9] .…”
Section: Clinical Outcomes In Hd: What Progress Have We Made?mentioning
confidence: 91%